HUBUNGAN MINAT BELAJAR DENGAN PEMAHAMAN SEJARAH LOKAL LAMPUNG PADA SISWA KELAS V SEKOLAH DASAR DI BANDAR LAMPUNG - SISKA, YULIA (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
This study aims to describe the significant relationship between interest in learning local history with understanding of local history. This research uses quantitative approach with Pearson correlation analysis. The population of this study were students of Class V Elementary School in Bandarlampung. The sample used amounted to 53 students. The technique used is puspossive sampling. The research instrument is a scale of  interests and understanding of local history. The data analysis technique used product moment analysis. The results showed that: There is a positive and significant correlation between Local Historical Learning Interest (X) with Understanding of Local History (Y) grade V SD student at Bandar lampung.